Solid state fermentation of domestic waste to produce organic acid - Sri Sarveshaa, Srirupan (2025)
Solid-state fermentation (SSF) has emerged as a sustainable method for valorizing domestic waste into value-added products, particularly organic acids. This study investigates the potential of SSF, utilizing Aspergillus niger as the microbial agent, to produce organic acids from domestic waste under controlled conditions. The research focuses on optimizing key parameters such as pH, temperature, moisture content, and aeration to maximize product yield. The experimental setup involved the preparation of domestic waste as the substrate, inoculation with A. niger, and fermentation over seven days. Quantitative analysis was performed using Dinitrosalicylic Acid (DNS) assay and High-Performance Liquid Chromatography (HPLC) to monitor glucose utilization and organic acid production. Results indicated a significant reduction in glucose concentration from 1.012 g/L on Day 1 to 0.287 g/L by Day 7, reflecting active microbial metabolism. HPLC analysis identified acetic acid and formic acid as predominant products, with acetic acid accounting for the highest peak area percentage of 65.94%. The study highlights the feasibility of SSF as an effective approach for domestic waste valorization, contributing to waste management and circular economy goals. Recommendations for further research include scaling up the process, enhancing microbial strains for higher yields, and integrating advanced downstream processing techniques to improve the recovery and purity of organic acids. This work underscores the potential of SSF to transform waste streams into valuable biochemical products, aligning with sustainable development practices.